PSYCHOLOGICAL ANALYSIS OF SELF-KNOWLEDGE PROBLEM - Kaminska, Olga (PSYCHOLOGICAL JOURNAL, 2017)
The article explores different concepts and points of view on the process of self-knowledge, determines its role in the formation and development of personality. The purpose of the article is to generalize scientific theories and views on the problem of self-knowledge. Much attention is paid to the study of the role of self-knowledge in the process of development of self-consciousness, as well as its influence on the formation of the «I-concept» and self-pacing personality. Self-knowledge is an important mechanism that ensures the development of self-awareness, allows the individual to form an adequate image of «I» to understand how it is appreciated by others. Emphasizes the relationship of self-knowledge and reflection. Reflection is analyzed as a philosophical concept and a psychological property of an individual. The types of reflection, their psychological essence and the specifics of influence on the formation of the personality are studied. The attention is paid to the disclosure of the peculiarities and conditions of the development of pedagogical reflection. Emphasis is placed on the value of existential reflection in the development of frustration states. Attention is drawn to the fact that the process of self-knowledge is inextricably linked with reflection, which can be considered in the broad sense - as a philosophical category, and in the narrow one - as a property of the individual, which allows it to objectively evaluate itself, to form an adequate self-assessment and self-esteem. The problem of self-knowledge is studied by many scholars, each of which focuses attention on its specific features, but they all claim that self-knowledge is a mechanism for the development of self-consciousness, which is a prerequisite for the formation of the individual, the formation of his individuality. Self-knowledge is considered as a mechanism for the development of self-consciousness, which allows to reflect successes and difficulties in the process of analysis of both their own personality as a whole, and the results of concrete activities, the success or failure of behavioral and social acts. This mechanism is activated as a result of the appearance of internal conflicts, the dissatisfaction with the personality of his position in the group or in society, the situations of frustration and the experience of cognitive dissonance, which leads to a change in the position of the individual to himself as a subject of knowledge, activity and communication. The product of self-knowledge is the search and creation of personality of new ideas about oneself, the expansion of the «I-concept», giving it a clearness, getting rid of ideas that are not consistent with each other. The result of this process is personal growth and self-perception.